HUBUNGAN KEMAMPUAN KOORDINASI MATA-TANGAN DAN KELINCAHAN TERHADAP KEMAMPUAN PUKULAN BACKHAND TENIS MEJA - Suryati Suryati; Andika Triansyah; Fitriana Puspa Hidasari; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to determine the relationship between eye-hand coordination and agility on the backhand ability of table tennis students who take extracurricular activities at SMA Negeri 9 Pontianak. SMA Negeri 9 Pontianak. This research method uses a descriptive method with a quantitative approach. This research was conducted at SMA N 9 Pontianak. The study was conducted in August 2020. The research subjects were 15 students of SMA Negeri 9 Pontianak extracurricular table tennis, sampling using all members of the population was used as the sample. This research technique uses measurement. Data analysis used quantitative descriptive data analysis techniques which were then interpreted qualitatively. The results of data analysis were obtained based on statistical calculations, Fcount = 18.08> Ftable = 3.89, so the results of this study can be concluded that in general there is a significant relationship between hand eye coordination and agility with backhand skills in table tennis for students. who took extracurricular activities at SMA Negeri 9 Pontianak. . Keywords: Agilit, backhand shot, hand eye coordination.